Audio Visual Application on Narrative Text’s Vocabulary Achievement on Tenth Grade Students of SMKN 5 Padang: Audio Visual Application On Narrative Text’s Vocabulary Achievement On Tenth Grade Students Of Smk N 5 Padang - Suri, Elda Martha; Mahalizikri, Irawan Fakhruddin; Pertiwi, Risa (Jurnal Pendidikan Indonesia, 2021)
Background: The low ability of students in achieving narrative text vocabulary. Objective: To discover whether understudies who are instructed utilizing sound visuals have superior lexicon accomplishment than understudies who are instructed utilizing routine media in the tenth grade of SMK N 5 Padang. Methods: This study uses a true experimental quantitative design method. The research design is a two-group pretest-posttest design. In this study, the population is class X SMK N 5 Padang. Results: Shows that students taught by Audio Visual have better vocabulary achievement in Narrative text than students taught by Conventional Media. in class X SMK N 5 Padang. Conclusion: The employment of audiovisual media in the teaching of vocabulary mastery was extremely effective when compared to traditional media.